Cerebral venous sinus thrombosis in patients with inflammatory bowel disease: a retrospective study - Wang Shujun (Nature Portfolio, 2021)
Abstract Cerebral venous sinus thrombosis (CVST) is a rare and devastating complication of inflammatory bowel disease (IBD). Early diagnosis and prompt treatment could improve prognosis. The aim of our study was to investigate the clinical data and predictive factors of inflammatory bowel disease in patients with a diagnosis of CVST. All IBD patient data were collected from July 2013 and September 2020. Clinical data, predictive factors and prognosis were compared between IBD patients with CVST and the IBD control group. The incidence of CVST in our study was 0.48%. The mean age of IBD patients with CVST was 34.9 years. The average duration of IBD was 4 years when cerebrovascular events occurred. The clinical presentation of CVST included headache (73.1%), vomiting (30.8%), limb dysmetria (26.9%), speech impairment (11.5%), blurred vision (7.7%), epileptic seizures (7.7%) and drowsiness (3.8%). The most common location for CVST was the transverse sinus (61.5%) followed by the superior sagittal sinus (30.8%). Anaemia, low albumin and elevated d-dimer were independent predictors of CVST in patients with IBD. Anticoagulation therapy was effective. The prognosis of IBD patients with CVST was worse than that of IBD patients without CVST. Early identification of the risk and clinical features of CVST in IBD patients is important. Prompt antithrombotic therapy is a safe and effective treatment.